2008
DOI: 10.1291/hypres.31.193
|View full text |Cite
|
Sign up to set email alerts
|

A Newly Estimated Glomerular Filtration Rate Is Independently Associated with Arterial Stiffness in Japanese Patients

Abstract: Chronic kidney disease (CKD) is associated with an increased risk of cardiovascular disease, and thus is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 27 publications
5
31
2
Order By: Relevance
“…15 CFPWV was not directly assessed in the Dutch study. Nakagawa et al, 20 in contrast to our findings, reported that arterial stiffness correlated with decreased eGFRcrea and increased with increasing stages of CKD (n ϭ 647, mean eGFRcrea 63.4 Ϯ 14.5 ml/min/1.73 m 2 , 37% with eGFRcrea Ͻ60 ml/min/1.73 m 2 ). Lack of CFPWV, exclusion of important metabolic parameters from multivariable models, and the use of hospital-based samples may account for the contrasting results.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…15 CFPWV was not directly assessed in the Dutch study. Nakagawa et al, 20 in contrast to our findings, reported that arterial stiffness correlated with decreased eGFRcrea and increased with increasing stages of CKD (n ϭ 647, mean eGFRcrea 63.4 Ϯ 14.5 ml/min/1.73 m 2 , 37% with eGFRcrea Ͻ60 ml/min/1.73 m 2 ). Lack of CFPWV, exclusion of important metabolic parameters from multivariable models, and the use of hospital-based samples may account for the contrasting results.…”
Section: Discussioncontrasting
confidence: 99%
“…These studies, however, have been limited by small samples of CKD subjects 16,17,19 -21 or the lack of data for carotid femoral pulse wave velocity (CFPWV), a gold standard measure of central arterial stiffness. 15,20 Therefore, the association of arterial stiffness and mild-to-moderate CKD warrants further examination.…”
mentioning
confidence: 99%
“…Some studies have shown that the arterial stiffness relates with age, body mass index, systolic blood pressure, diabetes and hypertension and independently associates decreased glomerular filtration rate. 36,37 A decreased excretion of EO in the patients with diminished glomerular filtration rate may be a further component of relationship between the declining glomerular filtration rate and increased arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…The ankle-brachial pulse wave velocity (baPWV) was measured using a waveform analyzer (VP-1000; Colin Co., Komaki, Japan) after at least 5 min of rest, as previously reported. 15 The body surface area was calculated according to the following formula: body surface area¼0.6Âheight (m)+0.0128Âweight (kg)-0.1529. Diabetes mellitus was defined based on the World Health Organization criteria.…”
Section: Methodsmentioning
confidence: 99%